Bulky hinges bracelet / Aida Nur Sabrina Adnan - Adnan, Aida Nur Sabrina (2022)
The motif, shape, from an artistic line on Batik sarung were transformed into jewelry box design though ideation and development of idea. Malaysian batik is batik textile art, particularly on the country's east coast (Kelantan, Terengganu and Pahang). Leaves and flowers are the most widely used motifs. Because Islamic tradition forbids using animal pictures as ornamentation, human or animal depictions in Malaysian batik are uncommon